Advanced Materials for Next‐Generation Spacecraft. Issue 50 (9th October 2018) - Levchenko, Igor; Bazaka, Kateryna; Belmonte, Thierry; Keidar, Michael; Xu, Shuyan
Abstract: Spacecraft are expected to traverse enormous distances over long periods of time without an opportunity for maintenance, re‐fueling, or repair, and, for interplanetary probes, no on‐board crew to actively control the spacecraft configuration or flight path. Nevertheless, space technology has reached the stage when mining of space resources, space travel, and even colonization of other celestial bodies such as Mars and the Moon are being seriously considered. These ambitious aims call for spacecraft capable of self‐controlled, self‐adapting, and self‐healing behavior. It is a tough challenge to address using traditional materials and approaches for their assembly. True interplanetary advances may only be attained using novel self‐assembled and self‐healing materials, which would allow for realization of next‐generation spacecraft, where the concepts of adaptation and healing are at the core of every level of spacecraft design. Herein, recent achievements are captured and future directions in materials‐driven development of space technology outlined. Abstract : Advanced materials are among the critical elements that determine efficiency, performance, and working life of space equipment. True interplanetary advances may only be attained using novel self‐assembled and self‐healing materials. In this context, recent achievements in the field are discussed, and future directions in materials‐driven development of space technology are outlined, with a particular emphasis on dynamic and self‐healing properties.